Pulverized river shellfish shells as a cheap adsorbent for removing of malathion from water: examination of the isotherms, kinetics, thermodynamics and optimization of the experimental conditions by the response surface method - Veličković, Zlate S.; Vujičić, Bogdan D.; Stojanović, Vladica N.; Stojisavljević, Predrag N.; Bajić, Zoran J.; Đokić, Veljko R.; Ivanković, Negovan D.; Otrisal, Pavel P. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: In this study, we investigated the possibility of removing the organophosphorus pesticide malathion from water using a new adsorbent based on the biowaste of river shell shards from the Anodonta Sinadonta woodiane family, a material that accumulates in large quantities as waste on the banks of large rivers. Two adsorbents were tested - mechanically comminuted river shells (MRM) and mechanosynthetic hydroxyapatite from comminuted river shells (RMHAp). Methods: The obtained adsorbents were characterized and tested for the removal of the organophosphorus pesticide malathion from water. In order to predict the optimal adsorption conditions using the Response Surface Method (RSM), the authors investigated the influence of variable factors (adsorption conditions), pH values, adsorbent doses, contact times, and temperatures on the adsorbent capacity. Results: The best adsorption of malathion was achieved at mean pH values between 6.0 and 7.0. The adsorption data for malathion at 25, 35, and 45 °C were compared using the Langmuir, Freundlich, Dubinin-Radushkevich (DR), and Temkin isothermal models, as well as pseudo-first order, pseudo-second order and Elovic kinetic models for modeling adsorption kinetics. The maximum Langmuir adsorption capacity for MRM and RMHAp at 25 °C was 46,462 mg g-1 and 78,311 mg g-1, respectively. Conclusion: The results have showed that malathion adsorption on both adsorbents follows the pseudo-second kinetic model and the Freundlich isothermal model. The thermodynamic parameters indicate the endothermic, feasible, and spontaneous nature of the adsorption process.